The sunshine girls eaudiobook A novel. - Fader, Molly (Harlequin Audio, 2022)
"A breathtaking story of an extraordinary friendship. Molly Fader has penned an unforgettable novel that is sure to be one of the year's best." —Kristy Woodson Harvey, New York Times bestselling author of The Wedding Veil Two friends. A lifetime of secrets. One sparkling story. 1967 Iowa. Nursing school roommates BettyKay and Kitty don't have much in common. BettyKay has risked her family's disapproval to pursue her dreams away from her small town. Cosmopolitan Kitty has always relied on her beauty and smarts to get by and to hide a painful secret. Yet the two share a determination to prove themselves in a changing world, forging an unlikely bond on a campus unkind to women. Before their first year is up, tragedy strikes, and the women's paths are forced apart. But against all odds, a decades-long friendship forms, persevering through love, marriage, failure, and death, from the jungles of Vietnam to the glamorous circles of Hollywood. Until one snowy night leads their relationship to the ultimate crossroads. Fifty years later, two estranged sisters are shocked when a famous movie star shows up at their mother's funeral. Over one tumultuous weekend, the women must reckon with a dazzling truth about their family that will alter their lives forever...